Existence of Fixed Point Results in 𝐺-Metric Spaces - Zead Mustafa; Wasfi Shatanawi; Malik Bataineh (International Journal of Mathematics and Mathematical Sciences)
The purpose of this paper is to prove the existence of fixed points of contractive mapping defined on 𝐺-metric space where the completeness is replaced with weaker conditions. Moreover, we showed that these conditions do not guarantee the completeness of 𝐺-metric spaces.